203k views
3 votes
Solve the equation below by factorising.
2m? - 11m + 5 = 0

1 Answer

3 votes

Answer:

m =
(1)/(2) , m = 5

Explanation:

assuming you mean

2m² - 11m + 5 = 0

consider the product of the factors of the m² term and the constant term which sum to give the coefficient of the m- term

product = 2 × 5 = 10 and sum = - 11

the factors are - 10 and - 1

use these factors to split the m- term

2m² - 10m - m + 5 = 0 ( factor the first/second and third/fourth terms )

2m(m - 5) - 1(m - 5) = 0 ← factor out (m - 5) from each term

(m - 5)(2m - 1) = 0 ← in factored form

equate each factor to zero and solve for m

2m - 1 = 0 ⇒ 2m = 1 ⇒ m =
(1)/(2)

m - 5 = 0 ⇒ m = 5

User Nadiyah
by
5.4k points